Improving leg power and Dolyo Chagi kick speed in Taekwondo using plyometric, SAQ, and circuit training methods - Fajar, Muhammad Kharis; Rusdiawan, Afif; Ar Rasyid, Muhammad Labib Siena (Jurnal Keolahragaan, 2023)
This study aimed to determine the effect of giving three different exercise methods (Plyometric, SAQ, and Traning Circuit) on increasing leg muscle power and dolyo chagi kick speed in taekwondo athletes. The research design used pre and post design with a total of 18 Unesa student taekwondo athletes as research subjects. The subjects were divided into three groups (PLY, SAQ, and ST) consisting of 6 athletes each. The PLY group performs plyometric; The SAQ group performs Speed, Agility, and Quickness; and the ST Group performs circuit training. Interventions were given to each group with 18 meetings with a frequency of 3 times each week. Data analysis using manova test assisted with R studio software. The results of this study showed that the average value of the increase in leg power and kick speed was the highest in the SAQ group respectively 2.95±2.40 watts and 1.30±0.80 m/s. The manova test showed a p value of 0.1239 which means that there is no significant difference from the three training methods to leg power and kick speed. In conclusion, plyomeric training methods, SAQ, and training circuits can increase dolyo chagi leg power and kick speed in taekwondo athletes, but there is no significant difference in the improvement.